(untitled) (Journal of Engineering, 2026)
Bridges are one of Baghdad’s most important infrastructure elements, today they are not only for crossing the river and connecting Karkh and Rusafa, but serve as strategic tools to ease traffic congestion resulting from population density and rapid urbanization. With a population exceeding eight million and a growing number of vehicles, maintaining and sustaining bridges through continuous monitoring and inspection has become essential. Yet the current inspection process faces many challenges. This research aims to identify factors hindering optimal bridge inspection and to provide solutions for improved inspection performance. These challenges stem from managerial, technological, economic and environmental issues, reducing reliability and efficiency. The study used literature review, interviews and a questionnaire completed by 65 experts and academics, with 50 responses statistically analyzed (mean, standard deviation, Cronbach’s alpha, Relative Importance Index). Findings show that the main managerial challenges are a lack of qualified technical leadership (RII = 91.2 %) and neglect of bridges for long periods (RII = 85.2 %). Technical constraints include a lack of analytical capacity, a shortage of competent inspectors and limited funds for modern inspection equipment. Further barriers include traffic congestion, poor coordination with stakeholders and environmental issues such as moisture-induced corrosion. Addressing these challenges requires strengthening management oversight, building inspection capacity, securing adequate funding, improving coordination with traffic management and incorporating environmental considerations to enhance inspection effectiveness and extend bridge life.